2021
DOI: 10.1186/s13049-021-00883-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sequence induction: where did the consensus go?

Abstract: Background Rapid Sequence Induction (RSI) was introduced to minimise the risk of aspiration of gastric contents during emergency tracheal intubation. It consisted of induction with the use of thiopentone and suxamethonium with the application of cricoid pressure. This narrative review describes how traditional RSI has been modified in the UK and elsewhere, aiming to deliver safe and effective emergency anaesthesia outside the operating room environment. Most of the key aspects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 77 publications
0
16
0
10
Order By: Relevance
“…The avoidance of adverse events during RSI and successful intubation of acutely ill patients on the first attempt can be influenced by operator-related factors, selection of airway equipment, and choice of medications; 18 hence, the choice of induction drug is dictated by hemodynamic considerations. 19 This is the first systematic review and meta-analysis to compare the safety and efficacy of etomidate and ketamine as induction agents for RSI with respect to post-induction hypotension and first-attempt intubation success in prehospital and emergency department settings.…”
Section: Discussionmentioning
confidence: 99%
“…The avoidance of adverse events during RSI and successful intubation of acutely ill patients on the first attempt can be influenced by operator-related factors, selection of airway equipment, and choice of medications; 18 hence, the choice of induction drug is dictated by hemodynamic considerations. 19 This is the first systematic review and meta-analysis to compare the safety and efficacy of etomidate and ketamine as induction agents for RSI with respect to post-induction hypotension and first-attempt intubation success in prehospital and emergency department settings.…”
Section: Discussionmentioning
confidence: 99%
“…Another piece of evidence supporting the use of cricoid pressure is the idea that the pressure applied inhibits air from entering the stomach, which reduces the risk of aspiration 71 . The conundrum is that although more research is needed to ascertain morbidity and mortality as they relate to the application of cricoid pressure, it is unethical to conduct large, prospective, randomized clinical trials with and without cricoid pressure on patients because the enrolled patient population would be patients at risk for regurgitation and aspiration—how would researchers ethically withhold cricoid pressure for patients in the control group? 2,11,34 These studies also would need to involve more than 50,000 patients to reduce the incidence of aspiration by 50%, and numerous variables would have to be standardized 41 …”
Section: Cricoid Pressurementioning
confidence: 99%
“…the airway to be secured rapidly and minimises air entry into the stomach, which can increase the risk of gastric regurgitation and aspiration of stomach contents. 1 RSI in the ED is a high-risk procedure with increased risk of complications such as oxygen desaturation, oesophageal intubation, pneumothorax, hypotension and cardiac arrest. 2 Patients presenting to the ED are often unfasted, which increases the risk of regurgitation and aspiration of gastric contents.…”
Section: Key Findingsmentioning
confidence: 99%
“…[5][6][7] Since its introduction, the use of CP has become controversial. 1 First, the anatomical and physiological basis of the manoeuvre has been challenged. MRI studies have shown that the oesophagus often lies laterally to the cricoid cartilage, leading to concerns that applying CP does not occlude the oesophagus.…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation